In vitro and physiologically‐based pharmacokinetic based assessment of drug–drug interaction potential of canagliflozin. (20th December 2016) - Mamidi, Rao N. V. S.; Dallas, Shannon; Sensenhauser, Carlo; Lim, Heng Keang; Scheers, Ellen; Verboven, Peter; Cuyckens, Filip; Leclercq, Laurent; Evans, David C.; Kelley, Michael F.; Johnson, Mark D.; Snoeys, Jan
Abstract : Aims: Canagliflozin is a recently approved drug for use in the treatment of type 2 diabetes. The potential for canagliflozin to cause clinical drug–drug interactions (DDIs) was assessed. Methods: DDI potential of canagliflozin was investigated using in vitro test systems containing drug metabolizing enzymes or transporters. Basic predictive approaches were applied to determine potential interactions in vivo . A physiologically‐based pharmacokinetic (PBPK) model was developed and clinical DDI simulations were performed to determine the likelihood of cytochrome P450 (CYP) inhibition by canagliflozin. Results: Canagliflozin was primarily metabolized by uridine 5′‐diphospho‐glucuronosyltransferase 1A9 and 2B4 enzymes. Canagliflozin was a substrate of efflux transporters (P‐glycoprotein, breast cancer resistance protein and multidrug resistance‐associated protein‐2) but was not a substrate of uptake transporters (organic anion transporter polypeptide isoforms OATP1B1, OATP1B3, organic anion transporters OAT1 and OAT3, and organic cationic transporters OCT1, and OCT2). In inhibition assays, canagliflozin was shown to be a weak in vitro inhibitor (IC50 ) of CYP3A4 (27 μmol l –1, standard error [SE] 4.9), CYP2C9 (80 μmol l –1, SE 8.1), CYP2B6 (16 μmol l –1, SE 2.1), CYP2C8 (75 μmol l –1, SE 6.4), P‐glycoprotein (19.3 μmol l –1, SE 7.2), and multidrug resistance‐associated protein‐2 (21.5 μmol l –1, SE 3.1). Basic models recommended in DDI guidelines (US Food & Drug Administration and European Medicines Agency) predicted moderate to low likelihood of interaction for these CYPs and efflux transporters. PBPK DDI simulations of canagliflozin with CYP probe substrates (simvastatin, S‐warfarin, bupropion, repaglinide) did not show relevant interaction in humans since mean areas under the concentration‐time curve and maximum plasma concentration ratios for probe substrates with and without canagliflozin and its 95% CIs were within 0.80–1.25. Conclusions: In vitro DDI followed by a predictive or PBPK approach was applied to determine DDI potential of canagliflozin. Overall, canagliflozin is neither a perpetrator nor a victim of clinically important interactions.